Decision Analysis of Abandonment and Site Retirement for Sand Plant Facilities Gathering Station - Tinamtu, Ali Rekso; Novani, Santi (Indonesian Journal of Multidisciplinary Science, 2023)
Aging infrastructure can pose risks to safety, environmental impact, and production efficiency. Therefore, PERTAMINA has implemented a comprehensive maintenance and inspection program for its oil and gas infrastructure in the Rokan Block. The company regularly inspects and tests its equipment to detect any potential issues and ensure that it is in a safe working condition. PERTAMINA also invests in the upgrade and replacement of aging infrastructure components to improve production efficiency and reduce environmental impact. The purpose of the study is to provide light on how sand plant facilities gathering station abandonment and site retirement decisions are made. A cross-sectional survey with a quantitative approach was employed as the research design for this study, and data were gathered from both primary and secondary sources. Based on the preliminary results of Simple Multiple Attribute Rating Technique (SMART) exercises, which were conducted to compare the benefits and drawbacks of each alternative, it was determined that alternative 2—disassembled and put in temporary storage as scrap—was the most appealing choice.